(untitled) (Research, Society and Development, 2020)
Introduction: Even after almost four decades of its discovery, the Acquired Immunodeficiency Virus (HIV) still has a high potential for morbidity and mortality, remaining among the main public health problems. In addition to the profile of people who are infected, the causes of death in this population have shown a trend beyond opportunistic diseases and cancer, such as chronic non-communicable diseases. Objective: To describe the profile of users and the main characteristics of deaths in a Specialized Assistance Service (SAE) of the Municipal Reference Center (CRM) for STD / HIV / AIDS in Feira de Santana, Bahia, Brazil. Materials and method: This is a sectional study, conducted based on data from a historical cohort. Sociodemographic, lifestyle, clinical complications, treatment and mortality variables obtained from these individuals’ medical records were analyzed. Results: The sample studied consisted of 199 individuals who started using antiretrovirals between 2003-2017. There was a predominance of males (63.8%), self-declared blacks (82.9%), median age 34 years (18-72 years), without a partner (61.9%), heterosexuals (69.5%) and 45.7% studied up to 9 years old (elementary school). HIV-related lethality was 7%. Conclusion: The late diagnosis and the high occurrence of cases with AIDS progression also called attention, mainly to a possible failure in the management of health care. In addition, opportunistic infections, co-infections and comorbidities have been identified that appear to compromise quality of life and increase the chance of death.